Investment and Capital Constraints: Repatriations Under the American Jobs Creation Act - Faulkender, Michael; Petersen, Mitchell (Review of Financial Studies, 2012)
[The American Jobs Creation Act (AJCA) significantly lowered U.S. firms' tax cost when accessing their unrepatriated foreign earnings. Using this temporary shock to the cost of internal financing, we examine the role of capital constraints in firms' investment decisions. Controlling for the capacity to repatriate foreign earnings under the AJCA, we find that a majority of the funds repatriated by capital-constrained firms were allocated to approved domestic investment. Although unconstrained firms account for a majority of repatriated funds, no increase in investment resulted. Contrary to other examinations of the AJCA, we find little change in leverage and equity payouts.]